Yogurt with passion fruit (Passiflora edulis) pulp and pectin added: effects on the viability of probiotic bacteria and on physicochemical, rheological and sensory properties - Freire, Vagna Aparecida Pereira; Massaut, Khadija Bezerra; Gandra , Tatiane Kuka Valente; Silva, Wladimir Padilha da; Fiorentini, Ângela Maria (Seven Editora, 2023)
This study aimed to evaluate the viability of probiotic cultures (Lactobacillus acidophilus, Bifidobacterium lactis) and their physicochemical, rheological, and sensory properties in yogurt with passion fruit pulp and pectin. Six treatments of yogurts were prepared, differing in the addition of passion fruit pulp and pectin and different combinations of starter and probiotic cultures. The addition of passion fruit pulp and pectin interfered in pH, acidity, syneresis, and viscosity but did not affect the viability of the probiotic cultures, and in the sensory evaluation, the evaluators accepted the yogurt well. The results obtained were promising, as in addition to the antioxidant potential and significant nutritional value, they allow the development of a new dairy product with the insertion of regional fruits. DOI:https://doi.org/10.56238/interdiinovationscrese-011